Human Amniotic Membrane in Ocular Surface Reconstruction: Biological Properties, Clinical Applications, and Future Perspectives - Kordylewska-Kubus, Angelika; Dobrowolski, Dariusz (Journal of Education, Health and Sport, 2026)
The human amniotic membrane (HAM) is the innermost layer of the placenta and has been extensively utilized in ophthalmology due to its anti-inflammatory, antimicrobial, antiangiogenic, and pro-regenerative properties. Rich in growth factors, cytokines, and stem cells, HAM supports corneal epithelial healing and modulates inflammatory responses, making it a valuable therapeutic option in the management of ocular surface disorders. Established clinical indications include chemical and thermal burns, corneal ulcers of various etiologies, corneal perforations, bullous keratopathy, and limbal stem cell deficiency. Conventional amniotic membrane transplantation remains a well-established surgical technique, with multiple application methods tailored to the depth and extent of corneal damage. In addition to sutured grafts, sutureless cryopreserved and dehydrated amniotic membrane devices mounted on ocular rings have expanded outpatient treatment options. More recently, amniotic membrane extract eye drops (AMEED) have emerged as a minimally invasive therapeutic approach, with preliminary studies demonstrating improvements in tear film parameters, ocular surface integrity, and symptoms in conditions such as dry eye disease and ocular chronic graft-versus-host disease. Despite promising clinical outcomes, significant challenges remain, including the lack of standardized extraction, preservation, and quality-control protocols for amniotic membrane derivatives. Variability in biological composition related to donor characteristics and processing methods may influence therapeutic efficacy. Further well-designed controlled clinical trials, standardization of manufacturing procedures, and long-term safety assessments are required to fully validate and integrate amniotic membrane–based therapies into routine ophthalmic practice.